2020
DOI: 10.1101/2020.04.13.037952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone variants in archaea and the evolution of combinatorial chromatin complexity

Abstract: Nucleosomes in eukaryotes act as platforms for the dynamic integration of epigenetic information. Post-translational modifications are reversibly added or removed and core histones exchanged for paralogous variants, in concert with changing demands on transcription and genome accessibility. Histones are also common in archaea. Their role in genome regulation, however, and the capacity of individual paralogs to assemble into histone-DNA complexes with distinct properties remain poorly understood. Here, we combi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…To place candidate histone hits in phylogenetic context, we added putative N. eucaryotum (SAG 55.87) histones to a large prior alignment of eukaryotic and archaeal histones [ 22 ] and subsequently built a phylogenetic tree (see Methods) from N. eucaryotum (SAG 55.87) candidate histones and the histones of C. variabilis NC64 , for which a high-quality genome assembly is available. We find candidate N. eucaryotum (SAG 55.87) histones that have high similarity to and cluster with C. variabilis H2A, H2B, H3 and H4 ( figure 1 ; electronic supplementary material, figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…To place candidate histone hits in phylogenetic context, we added putative N. eucaryotum (SAG 55.87) histones to a large prior alignment of eukaryotic and archaeal histones [ 22 ] and subsequently built a phylogenetic tree (see Methods) from N. eucaryotum (SAG 55.87) candidate histones and the histones of C. variabilis NC64 , for which a high-quality genome assembly is available. We find candidate N. eucaryotum (SAG 55.87) histones that have high similarity to and cluster with C. variabilis H2A, H2B, H3 and H4 ( figure 1 ; electronic supplementary material, figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…While in vivo studies have identified disparate roles of variant histones in archaea (27), very little is known about the structural modifications that they invoke. In a recent study by Stevens et al (28), molecular dynamics trajectories showed that substituting major type histones in Methanosphaera stadtmanae with a "capstone" paralog, a histone variant with sequence modifications at the four-helix bundle, disrupts the tetramer interface and separates histone dimers on a continuous DNA fragment, thereby limiting archaeasome size. In the context of the capstone model, our EM-derived structures suggest that destabilizing the fourhelix bundle interface may yield a subtle increase in DNA accessibility through increased exposure of the major groove, and without the need to fully displace the archaeasome subunit.…”
Section: Discussionmentioning
confidence: 99%
“…To place candidate hits in phylogenetic context, we added putative N. eucaryotum (SAG 55.87) histones to a large prior alignment of eukaryotic and archaeal histones (Stevens et al 2020) and subsequently built a phylogenetic tree (see Methods) from N. eucaryotum (SAG 55.87) candidate histones and the histones of C. variabilis NC64, for which a high quality genome assembly is available. We find candidate N. eucaryotum (SAG 55.87) histones that have high similarity to and cluster with C. variabilis H2A, H2B, H3, and H4 ( Figure 1).…”
Section: Wilhelm Personal Communication)mentioning
confidence: 99%
“…The remaining set of candidate histone-fold proteins were added to a pre-existing alignment of eukaryotic and archaeal histone-fold proteins (Stevens et al 2020) using Mafft v7.310 (add -reorder) along with annotated histones from C. variabilis NC64A obtained from Uniprot. A sub-alignment of candidate N. eucaryotum (SAG 55.87) and C. variabilis NC64A histones was extracted and used to build a maximum likelihood phylogenetic tree using .…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation